The Effect of Work Motivation and Work Discipline on Employee Performance at Store New Book Store, Malang Regency - Maria Fransiska Indi Yaning Kasman; Nur Ida Iriani; Moh. Askiyanto (International Journal of Management and Business, 2026)
This study aims to analyze the influence of work motivation and work discipline on employee performance at the New Book Store in Malang Regency. The background of this research is based on the important role of human resources in increasing the competitiveness of retail businesses, especially in the face of increasingly fierce competition. The problems identified relate to fluctuations in work motivation and the level of employee discipline, which have the potential to impact employee performance. Influence performance achievement. This study uses a quantitative approach with a survey method. The study population consisted of 35 employees and all were sampled using a census technique (total sampling). Data were collected through a questionnaire with a Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that work motivation and work discipline simultaneously have a significant effect on employee performance. Partially, work discipline has a positive and significant effect on employee performance, while work motivation has no significant effect partially. These findings indicate that discipline is a dominant factor in improving the quality, quantity, and responsibility of employee work. This study is expected to be a consideration for management in formulating performance improvement strategies through strengthening the discipline system and managing work motivation more effectively.